2020
DOI: 10.1111/ajt.16191
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous liver–kidney transplantation from donation after cardiac death donors: an updated perspective

Abstract: Early experiences with both liver and kidney donation after cardiac (DCD) allografts showed outcomes that were inferior to those for donation after brain death (DBD) donors. Concerns specific to DCD kidney allografts included prolonged delayed graft function (DGF), ischemia-reperfusion injury leading to allograft fibrosis, and primary nonfunction (PNF). 1-4 Similarly, decreased survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…26 Eleven patients in our cohort underwent SLK with a 1-y renal allograft survival of 72.7% that is lower than more contemporary reports. 27,28 All 3 graft losses occurred because of patient death; 2 of them happened early on in our experience (2005 and 2009) and were the result of graft versus host disease in 1 patient and cardiopulmonary arrest in the other.…”
Section: Discussionmentioning
confidence: 88%
“…26 Eleven patients in our cohort underwent SLK with a 1-y renal allograft survival of 72.7% that is lower than more contemporary reports. 27,28 All 3 graft losses occurred because of patient death; 2 of them happened early on in our experience (2005 and 2009) and were the result of graft versus host disease in 1 patient and cardiopulmonary arrest in the other.…”
Section: Discussionmentioning
confidence: 88%
“…There is always a concern about severe AKI resulting in fibrosis, but we do not see evidence in this cohort, likely due to younger donor age, lack of chronic changes seen on time 0 biopsy, and the possible effect of ischemic preconditioning 22,23 . Renal function was similar after month 1 in all 3 study groups.…”
Section: Discussionmentioning
confidence: 63%
“…There is always a concern about severe AKI resulting in fibrosis, but we do not see evidence in this cohort, likely due to younger donor age, lack of chronic changes seen on time 0 biopsy, and the possible effect of ischemic preconditioning. 22,23 Renal function was similar after month 1 in all 3 study groups. In previous studies, we have shown that the biomarkers of initial injury associated with kidneys from donors with AKI were transient and had resolved by 4 months.…”
Section: Discussionmentioning
confidence: 81%
“…123,124 Furthermore, the presence of DGF did not ultimately affect kidney or liver graft outcomes in patients transplanted with organs from donors with either brain death or cardiac death. 123 Thus, this encouraging data may help propel larger centers to reconsider the use of SLK DCD. Finally, use of DCD kidneys in combination with delayed implementation could potentially be an area in which the field of SLK evolves.…”
Section: Evolving Approaches To Improve Outcomes After Slkmentioning
confidence: 92%
“…122 Fortunately, more recent larger scale data demonstrate similar kidney graft and liver graft survival as well as overall patient survival for DCD SLK as compared with DBD of similar era. 123,124 Furthermore, the presence of DGF did not ultimately affect kidney or liver graft outcomes in patients transplanted with organs from donors with either brain death or cardiac death. 123 Thus, this encouraging data may help propel larger centers to reconsider the use of SLK DCD.…”
Section: Evolving Approaches To Improve Outcomes After Slkmentioning
confidence: 92%